2021
DOI: 10.3390/cancers13112578
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Anatomical Site and Sleep Quality

Abstract: Purpose: Sleep quality in relation to anatomic site among colorectal cancer (CRC) patients is not well understood, though discerning the relationship could contribute to improved survivorship care. Methods: We ascertained sleep quality (Pittsburgh Sleep Quality Index) and other personal characteristics within an ongoing population-based study of CRC patients identified through a cancer registry (N = 1453). Differences in sleep quality by CRC site were analyzed using chi-square and ANOVA tests. We used logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The Puget Sound SEER collects information on all cancers from residents across 13 counties in western Washington state. Participants in this study were diagnosed with CRC from April 1, 2016 to December 31, 2018 and were 20-74 years of age at the time of diagnosis [ 12 ]. Participants in the study were limited to those who were diagnosed with primary CRC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Puget Sound SEER collects information on all cancers from residents across 13 counties in western Washington state. Participants in this study were diagnosed with CRC from April 1, 2016 to December 31, 2018 and were 20-74 years of age at the time of diagnosis [ 12 ]. Participants in the study were limited to those who were diagnosed with primary CRC.…”
Section: Methodsmentioning
confidence: 99%
“…Among those identified, 541 patients (23%) declined to enroll, 294 (13%) were lost to contact, and 56 (2%) were deceased. A total of 1,454 (62%) patients consented and were enrolled [ 12 ]. For this study, we excluded individuals for whom complete medical record abstraction was not available ( N = 749).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of a long-term follow-up study (median of 8 years) of CRC patients ( n = 1575) highlighted that the hazard ratio and CRC-specific mortality of patients with a 5 g increase in daily fiber intake was 0.78 (95% CI, 0.65–0.93) and 0.86 (95% CI, 0.79–0.93), respectively [ 10 ]. Another study found that 70% of CRC patients ( n = 1453) reported sleep problems, which had a negative impact on health outcomes [ 11 ]. Wele et al [ 12 ] found that maintaining a normal body mass index (BMI), regular exercise, healthy eating habits, and minimizing alcohol and smoking slowed the progression of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Ton et al (2021) found that rectal cancer patients are more likely to have sleep complications compared to colon cancer patients. The authors suggest that sleep-focused survivorship care should be adapted according to the CRC site to ensure patients receive appropriate support [ 20 ]. Further, Roderburg et al (2021) evaluated the possibility of an association between cancer and dementia.…”
mentioning
confidence: 99%